Local Potential-Based Empowerment Through the Tapis Craft Center in Realizing Women's Independence in Tara-han Village, Katibung District, South Lampung Regency (International Journal of Economics and Management Research, 2026)
Women are valuable assets in the community, and their empowerment can improve welfare through activities that enhance their economic, social, and cultural roles. One such empowerment initiative is the tapis craft center in Tarahan Village, where women are trained in sewing and processing tapis, fostering their independence. This research focuses on how utilizing local potential through the tapis craft center empowers women. Using a descriptive qualitative approach, the study gathered data through observation, interviews, and documentation from 11 informants selected via purposive sampling. The findings indicate that the tapis craft center effectively supports women's independence by enhancing their skills and capacities. The empowerment process occurs in three stages: awareness, training, and mentoring. Awareness is raised through education about the economic and social benefits, as well as employment opportunities. In the training stage, women learn tapis making, embroidery, and marketing skills. Mentoring involves guidance from business owners, studio administrators, members, and the village head to supervise production activities. This empowerment leads to economic independence by providing additional income, social independence by boosting self-confidence, and cultural independence through the preservation of the tapis tradition across generations.